Religious Tolerance of Angan Sari Residents in Kutuh Village, Kintamani-Bangli - Rusmayani Rusmayani; Kusjuniati Kusjuniati; Novena Ade, F.S (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study is to reveal the religious tolerance that occurs between Hindus and Muslims in Banjar Angansari, Kutuh-Bangli and the challenges encountered in maintaining this tolerance. This type of research is descriptive qualitative, data obtained through interviews with community leaders of Hindus and Muslims in Kutuh. The results of the study show that: 1) the origin of Muslims in Kutuh Village due to muallaf who convert of Hindus to Islam in 1980, relationship base on filiation is the main factor in the growth of tolerance, and this is reflected in their daily lives. This tolerance has been maintained until now, 2) the challenge of religious tolerance through strengthening faith and religious practices that have been carried out by Muslim residents of Banjar Angansari Kutuh Village so that harmonious relations are established